2021
DOI: 10.1111/jrh.12558
|View full text |Cite
|
Sign up to set email alerts
|

Interstates of Infection: Preliminary Investigations of Human Mobility Patterns in the COVID‐19 Pandemic

Abstract: Purpose The COVID‐19 pandemic has illuminated various heterogeneities between urban and rural environments in public health. The SARS‐CoV‐2 virus initially spread into the United States from international ports of entry and into urban population centers, like New York City. Over the course of the pandemic, cases emerged in more rural areas, implicating issues of transportation and mobility. Additionally, many rural areas developed into national hotspots of prevalence and transmission. Our aim was to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…Initially, the outbreak spread in and around the inner ring. Previous literature also found that the COVID-19 pandemic in the United States was characterized by a geographically localized mosaic of transmission along an urban-rural gradient ( 8 - 9 ), suggesting that geographic distance may play an important role in SARS-CoV-2 spread. Finally, the public health impact of COVID-19 vaccines has already been widely discussed in the literature ( 10 - 13 ) and our study confirms previous evidence.…”
Section: Discussionmentioning
confidence: 91%
“…Initially, the outbreak spread in and around the inner ring. Previous literature also found that the COVID-19 pandemic in the United States was characterized by a geographically localized mosaic of transmission along an urban-rural gradient ( 8 - 9 ), suggesting that geographic distance may play an important role in SARS-CoV-2 spread. Finally, the public health impact of COVID-19 vaccines has already been widely discussed in the literature ( 10 - 13 ) and our study confirms previous evidence.…”
Section: Discussionmentioning
confidence: 91%
“…In reviewing epidemiological models using mobility data, we identified salient metrics of interest, including probability of infection [12], risk of importation [13], incubation period [15], mean importation rate [14], size at the epidemic peak [29], effective reproduction number [11], epidemic size [22], proportion of counties with at least one case [30], rate of spread [31], timing of the peak [32] and the average size of the peak [33].…”
Section: Methodsmentioning
confidence: 99%
“…4 However, as the pandemic evolved, cases were identified in rural areas, stemming from human road travel. 5 Some rural areas even became hotspots of disease or the source of focused outbreaks, such as in meat processing plants located in rural areas. 6 The pandemic created healthcare surges nationwide, including in urban, suburban, and rural areas, and posed significant challenges for infection preventionists (IP) who are charged with identifying, preventing, and controlling infectious disease transmission in healthcare settings.…”
Section: Introductionmentioning
confidence: 99%